Sexual Assault, Psychological Distress, and Protective Factors in a Community Sample of Black, Latinx, and White Lesbian and Bisexual Women - López, Gabriela (Journal of interpersonal violence, 2023)
Intersectionality and minority stress frameworks were used to guide examination and comparisons of psychological distress (depression, anxiety, posttraumatic stress disorder symptoms) and protective factors (religiosity, spirituality, social support) among 673 Black, Latinx, and White lesbian and bisexual women with and without histories of sexual assault. Participants were from Wave 3 of the 21-year longitudinal Chicago Health and Life Experiences of Women (CHLEW) study. More than one-third (38%) of participants reported having experienced adolescent or adult sexual assault (i.e., rape or another form of sexual assault) since age 14. Confirmatory factor analysis, structural equation modeling, and multivariate analyses of covariance were used to analyze the data. Results revealed that levels of religiosity/spirituality and psychological distress varied by race/ethnicity and by sexual identity (i.e., Black lesbian, Black bisexual, Latinx lesbian, Latinx bisexual, White lesbian, White bisexual). Black lesbian women reported the highest level of religiosity/spirituality whereas White lesbian women reported the lowest level. White bisexual women reported the highest level of psychological distress whereas White lesbian women reported the lowest level. We found no significant differences in reports of sexual assault or in social support (i.e., significant other, family, friend, and total social support). However, White lesbian women had higher friend, significant other, and total social support relative to the other five groups of women with minoritized/marginalized sexual identities. Future work should examine whether religiosity, spirituality, and social support serve as protective factors that can be incorporated into mental health treatment for lesbian and bisexual who have experienced sexual assault to reduce psychological distress.